Research progress of risk factors and nursing of diabetic nephropathy (糖尿病肾病患者危险因素及护理进展) - LI Shanshan (李珊珊); YANG Jianying (杨剑英) (中西医结合护理)
Diabetic nephropathy is one of the common microvascular complications in patients with diabetes, which is difficult to treat clinically, and is also a common cause of end-stage renal failure. This article discussed the long-term care of patients with diabetic nephropathy and its research progress, including the risk factors of diabetic nephropathy and nursing measures, in order to provide a reference for the nursing of diabetic nephropathy, so as to improve the quality of life of diabetic nephropathy population. (糖尿病肾病是糖尿病患者常见的微血管并发症之一, 临床治疗相对困难, 也是导致患者发生终末期肾功能衰竭的常见病因。本文探讨了糖尿病肾病患者长期护理及其研究进展, 包括糖尿病肾病的危险因素和对应护理措施等, 旨在为糖尿病肾病的护理提供参考, 以改善糖尿病肾病人群的生命质量。)